2019
DOI: 10.1075/ml.19019.ham
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of episodic memory to novel word learning

Abstract: Multiple theories predict that word learning is intimately linked to episodic memory, at least in the early phases of learning. However, it is unclear to what degree this link reflects more domain-specific (i.e., those dedicated to language or the lexicon) or more domain-general episodic memory processes that operate outside of language. One way to address this possibility is by using a behavioral individual differences design. This study examined whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…They also found that individual differences in nonlinguistic episodic memory abilities predicted vocabulary knowledge immediately after exposure. Unlike Hamrick et al (2019), though, Murphy et al (2021) found that episodic memory was a significant predictor of lexical abilities 2 days later. It is not clear whether the differences in outcomes between these studies are due to differences in study design or an unclear episodic memory effect, or both.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…They also found that individual differences in nonlinguistic episodic memory abilities predicted vocabulary knowledge immediately after exposure. Unlike Hamrick et al (2019), though, Murphy et al (2021) found that episodic memory was a significant predictor of lexical abilities 2 days later. It is not clear whether the differences in outcomes between these studies are due to differences in study design or an unclear episodic memory effect, or both.…”
Section: Introductionmentioning
confidence: 87%
“…Participants' episodic memory abilities were assessed with the continuous visual memory task (CVMT; Trahan & Larrabee, 1988), which has been employed in several studies looking at individual differences in episodic memory and language (e.g., Hamrick et al, 2019; Morgan‐Short et al, 2014; Murphy et al, 2021). The CVMT examines continuous recognition memory for abstract shapes.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations